Evaluation of the bond strengths of 3 endodontic cements via push-out test - De Souza Ferreira, Nadia; Di Iorio Jeronymo Ferreira, Raffaela [UNESP]; Da Rosa, Patricia Campos Ferreira [UNESP]; Gomes, Ana Paula Martins [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; Carvalho, Claudio Antonio Talge [UNESP]; Valera, Marcia Carneiro [UNESP] (My University, 2015)
In this study, the push-out method was used to evaluate the bond strengths of 3 types of endodontic cements according to their composite base: methacrylate, epoxy resin, and an experimental copaiba oil resin. The study hypothesis was that the methacrylate-based and experimental cements would have bond strengths equal to or greater than that of the epoxy resin-based cement. Thirty bovine tooth roots, 18 mm long, were divided into 3 groups (n = 10) based on the chosen cement treatment. After treatment, the specimens were sectioned and submitted to a push-out test. Results showed that there was no statistically significant difference (P < 0.05) between the cements used or between the middle and apical thirds of the roots. It could be concluded that the tested cements had satisfactory and similar bond strengths to dentin.
Keywords: Dentinal bonding; Endodontics; Root canal